ОСНОВНІ ЗАСАДИ СТВОРЕННЯ УМОВ ЕФЕКТИВНОГО ФУНКЦІОНУВАННЯ РИНКУ ПРАЦІ УКРАЇНИ - Perepelyukova, O.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2015)
The article discusses the basic principles of creating conditions conducive to improving labor market conditions to increase the level of employment and reducing unemployment. The main problem arising in the present conditions on regional labor markets in Ukraine. Thesis there is determined the main directions, which is necessary to create conditions for more efficient use of their potential. The basic measures to create conditions in the labor market that promote flexibility and labor mobility at national, regional and enterprise level. REFERENCES